Influence of turning cutting parameters on surface deformation of annealed AISI-1020 steel - Omar Zurita; Verónica Di Graci; Maria Capace (Revista Facultad de Ingeniería Universidad de Antioquia)
This paper presents a study on the influence of the cutting parameters (depth of cut, feed rate, and cutting speed) of turning with a carbide insert on the plastic deformation induced in annealed AISI-1020 steel. The results showed an increase in the deformation with each cutting parameter, due to the higher forces associated with the machining process and the cutting area. This causes an increase in the energy required for material cutting and, consequently, more cold work on the machined surface. The ANOVA analysis of the results showed that the feed rate had the most significant role in the resulting deformation (86.03%), and the cutting speed contributed less (6.81%). In addition, a mathematical expression for the prediction of deformation based on the evaluated parameters is proposed.